Ghana's chili market - Ministry of Food and Agriculture, Ghana; International Food Policy Research Institute; Amewu, Sena; Arhin, Eunice; Danso, Jane; Doughan, Roland Ato; Nafrah, Christiana; Owusu, Ivy; Pauw, Karl (International Food Policy Research Institute, 2020)
Chili pepper (Capsicum spp.) is an important spice and condiment used in many Ghanaian dishes. Alongside tomato and onion, chili ranks as one of Ghana’s three most important vegetable crops in terms of hectarage and crop value with significant potential for generating income, creating jobs, and contributing to foreign exchange through exports (Gonzalez et al. 2014). As is the case with other vegetable crops, chili production in Ghana is more profitable than producing traditional staple crops, such as maize and rice (Van Asselt et al. 2018). However, supply is highly seasonal as most production is rainfed. Chili yields in Ghana are also well below their potential. The government of Ghana has recognized this underexploited potential by designating chili as a priority crop under the Planting for Food Jobs (PFJ) initiative.